A LOOK AT THE LOSS CARRY-FORWARD. - Van Horne, James C. (The Accounting Review, 1963)
Abstract This article focuses on the U.S. federal income tax provision of loss carry forward. The operating loss carry-forward is a provision for the off-setting of a prior-year loss against current profits. This provision has created the accounting problem of how the tax reduction arising from the carry-forward should be treated on financial statements and, more particularly, on the profit and loss statement. The problem concerns the investor, the creditor, and the other readers of financial statements of companies utilizing the carry-forward. The importance of the loss carry-forward provision to a company is, of course, that it preserves valuable cash which otherwise would have to be paid out in taxes. Such funds are retained in the business and can be used for working capital and/or expansion of fixed or other non-current assets. A company which has alternate profit and loss years of about the same dimension would pay no tax at all. Consequently, this study is directed toward eliminating such confusion by finding the best method of treating the tax reduction arising from the carry-forward.